DEVELOPMENT STRATEGY AGRICULTURE BUSINESS - Wicaksana, Dafrian; Sya’roni, Deden A. Wahab (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Horticulture is the planning, development, protection, business, empowerment and financing activities related to fruit plants, vegetables, ornamental plants, and biopharmaceutical plants. The high competitiveness in the field of Horticulture results in a company needing a strategy in developing its business to be able to compete with its competitors, therefore the aim of this research is to see what factors influence marketing in a horticultural company and what strategies are appropriate for developing a horticultural business .The method used in this research is SWOT matrix analysis with the results of the research showing that the company is on a Grow and Develop strategy, namely with a strategy to improve product quality, improving good relationships with distributors or suppliers, improving the company’s organizational structure, then expanding the market to make it more developed and advanced